PENGARUH LATIHAN FISIK SENAM KAKI TERHADAP PENURUNAN KADAR GULA DARAH PADA PENDERITA DIABETES MELITUS TIPE II DI PUSKESMAS SENTOSA BARU - Harefa, Esti Pinta Sari; Simatupang, Lenny Lusia (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Background: Type II Diabetes Mellitus is a disease characterized by high blood sugar levels due to insulin resistance or impaired insulin production by the pancreas. One non-pharmacological therapy that can be done is foot exercises. This study aims to determine the effect of physical exercise on leg exercises on reducing blood sugar levels in people with Type II Diabetes Mellitus. The method used was a pre-experiment with a Two Group Pre-test and Post-test design with a control group. The research was conducted at the Sentosa Baru Community Health Center with a total of 24 respondents, divided into 12 intervention groups and 12 control groups. Blood sugar levels were measured before and after the intervention using a glukotest. The results of the study showed that there was a significant reduction in blood sugar levels in the group that did leg exercises compared to the control group that did not do this exercise. Data analysis used the Independent T-Test, which showed a p value <0.05, indicating a significant effect of leg exercise on reducing blood sugar levels. The results of this study indicate that foot exercises can be an effective non-pharmacological therapy in controlling blood sugar levels in people with Type II Diabetes Mellitus. Therefore, this exercise can be recommended as a health intervention that is easy, cheap, and can be done independently by diabetes patients to help manage their disease.